(untitled) (Proceedings OPTIMAL, 2026)
Health is a fundamental human right guaranteed by the state and constitutes one of the main indicators of national development. Bireuen Regency, as an autonomous region in Aceh Province, faces various challenges in the health sector, including unequal access to health services, limited availability of health personnel, and persistent issues related to nutrition and maternal and child health. This study aims to analyze the implementation of health policies in Bireuen Regency and to assess the effectiveness of the programs that have been implemented. The study employs a descriptive quantitative approach supported by qualitative analysis. Quantitative data were obtained from official reports of the Bireuen Regency Health Office, Statistics Indonesia (BPS), the Regional Medium-Term Development Plan (RPJMD), and the Ministry of Health of the Republic of Indonesia. The indicators analyzed include the number of health facilities and health personnel, coverage of National Health Insurance (JKN) membership, regional health budget allocation, and public health status indicators such as infant mortality rate, life expectancy, and stunting prevalence. Qualitative analysis was conducted through a review of policy documents and relevant literature to evaluate the alignment between program planning and performance outcomes. The results show that health services in Bireuen Regency are predominantly provided by primary healthcare facilities, such as community health centers (puskesmas) and integrated service posts (posyandu), which play a strategic role in promotive and preventive efforts. Health personnel are dominated by nurses and midwives, while the number of specialist doctors remains limited, resulting in suboptimal referral and specialized health services. JKN membership coverage increased by 4.7% over a three-year period, life expectancy showed an upward trend, while infant mortality rates and stunting prevalence declined, although stunting remains a significant public health concern. Health budget allocation demonstrates an increasing trend and has exceeded 10% of the regional budget (APBD), reflecting the local government’s commitment to health sector development. In conclusion, health policies in Bireuen Regency have shown positive outcomes in improving access to and quality of health services. However, challenges remain in achieving equitable distribution of specialist health personnel and further reducing stunting prevalence. Increased budget allocation and strengthened needs-based planning are key to ensuring the sustainability of health programs and improving overall public health status.